2021
DOI: 10.7150/thno.52442
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics identify arachidonic-acid-regulated signal transduction pathways modulating macrophage functions with implications for ovarian cancer

Abstract: Arachidonic acid (AA) is a polyunsaturated fatty acid present at high concentrations in the ovarian cancer (OC) microenvironment and associated with a poor clinical outcome. In the present study, we have unraveled a potential link between AA and macrophage functions. Methods: AA-triggered signal transduction was studied in primary monocyte-derived macrophages (MDMs) by phosphoproteomics, transcriptional profiling, measurement of intracellular Ca 2+ accumulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 106 publications
2
25
0
Order By: Relevance
“…In fact, we showed that, besides the effect on cell invasion and 3D growth, buteinmodulated TWIST1 affects cisplatin resistance. A similar effect has recently been shown in epithelial ovarian cancer cells, where TWIST1 delineates a chemoresistant ovarian cancer phenotype [48][49][50] .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In fact, we showed that, besides the effect on cell invasion and 3D growth, buteinmodulated TWIST1 affects cisplatin resistance. A similar effect has recently been shown in epithelial ovarian cancer cells, where TWIST1 delineates a chemoresistant ovarian cancer phenotype [48][49][50] .…”
Section: Discussionsupporting
confidence: 66%
“…Such findings are in line with what we and others showed on the anticancer action of butein, i.e., that it inhibits migration, invasion, clonogenicity, and resistance of the cells to chemo-therapeutics [18] . The effect of butein on TWIST1 matches what is known of the ability of TWIST1 to impinge on AKT signaling and drive resistance to cisplatin [50] . However, this may not be the only mechanism for butein: for example, target prediction of the buteinmodulated microRNAs suggested that additional targets may mediate the chemo-sensitization effect of butein (data not shown).…”
Section: Discussionsupporting
confidence: 55%
“…AA is a polyunsaturated fatty acid present at high concentrations in the OC microenvironment and associated with poor clinical outcomes. Several studies support its utility as a therapeutic target for intervention and prognostic indicator of OC (103). However, an MR study on female patients of European descent revealed no association of AA with OC risk (38).…”
Section: Arachidonic Acidmentioning
confidence: 99%
“…Finally yet importantly, the data shown here may be relevant for other chronic inflammation-related neoplasms. For example, the levels of AA in peritoneal fluids from ovarian carcinoma patients were shown to hold prognostic value [ 81 ] and a recent “omics” profiling of ovarian cancer-derived, AA treatment of mononuclear cells revealed important pathway activation, among all deregulation of MAPK and Rho-GTPase signaling [ 82 ]. Additionally AA secreted by adipocytes, inhibited cisplatin-induced apoptosis of ovarian cancer cells [ 83 ], further supporting our observations.…”
Section: Discussionmentioning
confidence: 99%